2003
DOI: 10.1016/s1534-5807(03)00189-8
|View full text |Cite
|
Sign up to set email alerts
|

jumonji Downregulates Cardiac Cell Proliferation by Repressing cyclin D1 Expression

Abstract: Spatiotemporal regulation of cell proliferation is necessary for normal tissue development. The molecular mechanisms, especially the signaling pathways controlling the cell cycle machinery, remain largely unknown. Here, we demonstrate a negative relationship between the spatiotemporal patterns of jumonji (jmj) expression and cardiac myocyte proliferation. cyclin D1 expression and cell proliferation are enhanced in the cardiac myocytes of jmj-deficient mutant embryos. In contrast, jmj overexpression represses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 33 publications
4
130
1
Order By: Relevance
“…Cardiac myocytes in trabecular layer showed hyperproliferation in our jmj mutant mice Toyoda et al, 2003). From analysis of the hyperproliferation, we found that jmj expression starts at the stages when cell proliferation of cardiac myocytes starts to decrease in normal embryos and that cell proliferation and expression of cyclin D1, the gene that encodes one of the G1 cyclins, are not repressed in jmj embryos (Toyoda et al, 2003). jmj overexpression by transgenesis represses cyclin D1 expression in the heart.…”
Section: Jmj Functions In Cardiac Developmentmentioning
confidence: 75%
See 4 more Smart Citations
“…Cardiac myocytes in trabecular layer showed hyperproliferation in our jmj mutant mice Toyoda et al, 2003). From analysis of the hyperproliferation, we found that jmj expression starts at the stages when cell proliferation of cardiac myocytes starts to decrease in normal embryos and that cell proliferation and expression of cyclin D1, the gene that encodes one of the G1 cyclins, are not repressed in jmj embryos (Toyoda et al, 2003). jmj overexpression by transgenesis represses cyclin D1 expression in the heart.…”
Section: Jmj Functions In Cardiac Developmentmentioning
confidence: 75%
“…For example, strong expression can be detected in many neurons after final mitosis in the cerebrum and cerebellum (Takeuchi et al, 1995;Takeuchi, 1997). jmj expression starts when the levels of cell proliferation start to decrease in cardiac myocytes in the ventricles (Toyoda et al, 2003). A more typical expression pattern can be seen in the lens (Fig.…”
Section: Jmj Expression Pattern During Developmentmentioning
confidence: 95%
See 3 more Smart Citations